Farmers Perception on the Services of Farmer Producer Organisations (FPOs) in Anantapuram District of Andhra Pradesh - Ravikishore, M.; Royal, A. Prudvi; Gopal, P. V. Satya; Johnson, M.; Seedari, Ujwala Rani; Subbaiah, K. Rama; Supriya, P.; Rani, K. Sudha (International Journal of Bio-resource and Stress Management, 2024)
A study was conducted during September, 2020 to August, 2022 in the Anantapuramu district of Andhra Pradesh, India to analyze the farmers perception on the services of Farmer Producer Organizations (FPOs). Five FPOs namely Sri Venkateswara Swamy FPO, Sri Peddamma Thalli FPO, Sri Ramaswamy FPO, Narpala Rythunestam FPC ltd and Tadipatri Horticulture FPO were selected randomly as they are actively functioning in the district. An interview schedule was developed to collect the information from selected FPOs through purposive cum simple random sampling. From each FPO, fifteen farmer members were randomly selected and thus, comprising a sample size of 75 farmers from five FPOs. The findings of the study revealed that the majority of the members (64%) had perceived that FPOs performance with respect to their input services was medium, whereas 72% of them had agreed with respect to technical services as medium. With respect to financial services, 62.67% members perceived that FPOs performance was medium, more than half of the members (54.67%) had consented to marketing services as medium and more than 62.67% agreed with the processing and value addition services as medium. In respect to all the services, 65.33% agreed with the performance of FPOs was proved as medium whereas 18.67% of members had received high level of services and 16% of members found it as low.